Substance Use Disorders and Behavioral Addictions During the COVID-19 Pandemic and COVID-19-Related Restrictions - Avena, Nicole M.; Simkus, Julia; Lewandowski, Anne; Gold, Mark S.; Potenza, Marc N. (Frontiers in Psychiatry, 2021)
COVID-19 was first identified in Wuhan, China in December of 2019 and appeared in the United States one month later (Centers for Disease Control and Prevention, 2020). Between the onset of the pandemic and January 13, 2021, over 92 million people have tested positive for the virus and over 1.9 million people have died globally (Worldometer, 2021). Virtually every country in the world has been impacted by this virus. Beginning in March 2020, many U.S state governments enforced a “quarantine” to respond to the growing health crisis. Citizens were required to remain at home; schools, restaurants, and non-essential businesses were forced to close, and large gatherings were prohibited. Americans’ lives were transformed in a span of days as daily routines were interrupted and people were shuttered indoors. Mounting fear and unpredictability coupled with widespread unemployment and social isolation escalated anxiety and impacted the mental health of millions across the globe. Most (53%) U.S adults reported that the coronavirus outbreak has had a negative impact on their mental health, including inducing or exacerbating use of alcohol, drugs, gambling and overeating as coping mechanisms (Hamel et al., 2020). In this paper, we will examine substance use and addictive behaviors that have been used to manage the stress and uncertainty wrought by the COVID-19 pandemic. We review the changing treatment landscape as therapy pivoted online and telemedicine became the norm.